Student Mobility Across Schools and its Links to Underachievement - Sylvia Dixon (New Zealand Government, The Treasury, 2018)
This paper provides information on the extent of student mobility between schools in New Zealand, measuring mobility rates at both the student and school level. It explores the characteristics of mobile students, the extent to which they become disengaged from school, and their NCEA level 1 achievement rates. It also compares the student turnover rates of different types of schools. We find that mobile students make up a sizeable sub-group within the set of students who do not achieve NCEA level 1. Analysing data for the 1998 birth cohort, we find that mobile students (defined as those attending five or more schools while aged 8-14 years) represented 9% of all students, but 26% of those who did not achieve NCEA level 1. The association of mobility with poorer attainment means that strategies to raise student achievement must work well for children who change schools frequently, as well as for children with more stable schooling patterns. At the school level, we find large variations between schools in student turnover rates and in the proportion of students who are frequent movers. Because high student turnover increases a school's workload and costs and the complexity of teaching, it could have implications for the schooling system in areas such as resourcing, learning support and information exchange.
Keywords: I21; 330; Transience; mobility; achievement; schools